Experimental Tailoring of Structural and Optoelectronic Properties in Doped Semiconductor Nanostructures for High-Performance Nano-Devices - Zainab SH. Mohammed; M.H. Asmaa; Zainab SH. Mohammed (Jurnal MIPA dan Pembelajarannya, 2026)
Because of their high crystal structure, energy gap, and charge transfer tunability, doped semiconductor nanostructures provide a potential sector for the development of high-performance nanodevices, especially photodetectors and optoelectronic applications. The fact that the impact of ion doping is not necessarily positive or linear presents a significant research problem. While high concentrations may restrict device efficiency by increasing defects, lattice distortion, and dark current, low concentrations may enhance characteristics. The objective of this study was to ascertain the ideal concentration for improving nanodevice performance as well as to examine the impact of various doping concentrations on the structural and optoelectronic characteristics of ZnO nanostructures. Undoped and doped samples at 1, 3, and 5% concentrations were prepared using sol-gel spin coating, then thermally treated and analyzed using XRD, SEM/EDX, UV-Vis, PL, and electrical measurements. Photodetectors were also fabricated to evaluate the optical response. The results showed that a concentration of 3% performed best, increasing the crystalline size from 24.8 to 32.6 nm, decreasing the energy gap from 3.27 to 3.12 eV, reducing the resistivity from 8.4 × 10⁻² to 1.9 × 10⁻² Ω·cm, and increasing the photoresponsivity from 0.18 to 0.92 A/W. These results indicate that the medium doping provides an effective balance between improving crystallinity, adjusting the energy gap, and enhancing charge transfer